2017
DOI: 10.1038/emm.2016.168
|View full text |Cite|
|
Sign up to set email alerts
|

Alectinib (CH5424802) antagonizes ABCB1- and ABCG2-mediated multidrug resistance in vitro, in vivo and ex vivo

Abstract: Alectinib, an inhibitor of anaplastic lymphoma kinase (ALK), was approved by the Food and Drug Administration (FDA) for the treatment of patients with ALK-positive non-small cell lung cancer (NSCLC). Here we investigated the reversal effect of alectinib on multidrug resistance (MDR) induced by ATP-binding cassette (ABC) transporters, which is the primary cause of chemotherapy failure. We provide the first evidence that alectinib increases the sensitivity of ABCB1- and ABCG2-overexpressing cells to chemotherape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…First-generation ALK inhibitor crizotinib was shown to enhance the efficacy of doxorubicin and paclitaxel via ABCB1 inhibition in vitro and in vivo, respectively [35]. In addition, second-generation ALK inhibitors ceritinib and alectinib were both described as dual ABCB1 and ABCG2 inhibitors able to potentiate anticancer effects of chemotherapeutic drugs, which are substrates of these transporters [36,37]. Noteworthy, these properties are not limited only to ALK inhibitors but were observed also in TKIs hitting other targets, such as epidermal growth factor receptor (EGFR) inhibitor gefitinib, vascular endothelial growth factor receptor (VEGFR) inhibitor sorafenib and several others [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…First-generation ALK inhibitor crizotinib was shown to enhance the efficacy of doxorubicin and paclitaxel via ABCB1 inhibition in vitro and in vivo, respectively [35]. In addition, second-generation ALK inhibitors ceritinib and alectinib were both described as dual ABCB1 and ABCG2 inhibitors able to potentiate anticancer effects of chemotherapeutic drugs, which are substrates of these transporters [36,37]. Noteworthy, these properties are not limited only to ALK inhibitors but were observed also in TKIs hitting other targets, such as epidermal growth factor receptor (EGFR) inhibitor gefitinib, vascular endothelial growth factor receptor (VEGFR) inhibitor sorafenib and several others [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Alectinib, an inhibitor of ALK, was approved by FDA for the treatment of NSCLC in 2015. In order to investigate whether alectinib could reverse ABCB1-mediated MDR in ex vivo, Yang et al collected ABCB1-overexpressing bone marrow samples from 4 resistance patients with AML or CML, and found that alectinib potently resensitized these drug resistant samples to Rhodamine 123, doxurubin and verapamil through MTT assays analysis [ 90 ], suggesting alectinib is able to reverse ABCB1-mediated MDR phenotype in primary leukemia cell.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that TKIs also bind to ATP binding site of ABC transporter. In recent years, we have demonstrated that a number of TKIs, including lapatinib [ 12 ], alectinib [ 13 ] and apatinib [ 14 ], can be used to potentiate the efficacy of anticancer drugs in MDR cancer cells by inhibiting ABC transporters. The line of research suggested that TKIs may be developed into useful agents for circumventing MDR.…”
Section: Introductionmentioning
confidence: 99%